2022
DOI: 10.1055/s-0042-1750139
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift: Outcomes of Early Autologous Breast Reconstruction after Radiation Therapy

Abstract: Background Radiation creates significant challenges for breast reconstruction. There is no consensus regarding optimal timing for autologous reconstruction following radiation. This study explores clearly defined, shorter time intervals between completion of radiation and reconstruction than previously reported. Methods A retrospective review was performed on patients who underwent autologous reconstruction by five microsurgeons at an academic institution from 2009 to 2020. Cohorts were selected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…33 Additionally, at a single academic institution, Elver et al demonstrated the efficacy of early reconstruction in patients receiving radiation, reporting lower levels of wound complications in those who received reconstruction in less than 3 months, though this finding was nonsignificant as the study was underpowered ( p > 0.05). 34 Our study builds upon these findings performed across multiple institutions with statistical significance, illustrating reconstruction may be safely performed in the 0 to 3 month period after PMRT. In a retrospective study of 189 patients, Baumann et al demonstrated that waiting longer than 12 months after the completion of PMRT was associated with fewer complications, but the earliest reconstruction in this study was performed at 3 months, and the authors did not conduct a subgroup analysis of the women reconstructed within 12 months.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…33 Additionally, at a single academic institution, Elver et al demonstrated the efficacy of early reconstruction in patients receiving radiation, reporting lower levels of wound complications in those who received reconstruction in less than 3 months, though this finding was nonsignificant as the study was underpowered ( p > 0.05). 34 Our study builds upon these findings performed across multiple institutions with statistical significance, illustrating reconstruction may be safely performed in the 0 to 3 month period after PMRT. In a retrospective study of 189 patients, Baumann et al demonstrated that waiting longer than 12 months after the completion of PMRT was associated with fewer complications, but the earliest reconstruction in this study was performed at 3 months, and the authors did not conduct a subgroup analysis of the women reconstructed within 12 months.…”
Section: Discussionmentioning
confidence: 60%
“…17 Exploring the possibility of earlier reconstruction, Elver et al recently published their single-institution experience of 462 radiated patients and did not find a difference in acute and late postoperative complications amongst patients undergoing reconstruction <3 months after radiation compared with those undergoing reconstruction at later intervals. 34 A limitation of this study, as has been the case in others, is the relatively small sample size (69 patients in the <3 month group) in some of the early reconstruction groups of patients.…”
Section: Discussionmentioning
confidence: 89%
“…Many studies have tried to evaluate the effect of the timing of radiation therapy in relation to the timing of breast reconstruction with mixed results reported. [31][32][33] Additionally, the need for This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tried to evaluate the effect of the timing of RT in relation to the timing of breast reconstruction with mixed results reported. [28][29][30] Additionally, the need for postoperative radiation has led many surgeons to favor the delayed-immediate approach with in an attempt to improve their aesthetic results and decrease their overall complications while getting patients into adjuvant treatment as expeditiously as possible. 31,32 There is sparse literature on the exact effects of unilateral radiation on the aesthetic outcomes of autologous breast reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Some breast cancer surgeons use the 3-month point after radiation if acute inflammation has resolved in order to expedite reconstruction. 5 The literature on the subject is almost exclusively limited to breast cancer reconstruction.…”
Section: Preoperative Management Of Soft Tissue Envelopementioning
confidence: 99%